Immunopathogenesis of Lung in Fatal COVID-19 Cases in Erbil, Iraq - Rasheed , Taban Kamal; Amin, Zahra Abdulqader; Sharef, Tuqa Yousif; Saleh, Lana Sardar (Iraqi Journal of Science, 2024)
Coronavirus disease 2019 (COVID-19) infection is caused by severe acute respiratory syndrome coronavirus-2 (SARS-Cov-2). It is characterized by respiratory distress, multiorgan dysfunction and death in some cases. The host immune response to SARS-CoV-2 appears to play a critical role in disease pathogenesis and clinical manifestation. However the pathological mechanism underling the disease has not been fully defined. Lung autopsy samples from 3 patients with fatal COVID-19 were evaluated using hematoxylin and eosin stain to analyze the histopathological changes. While immunohistochemical (IHC) staining was performed for detecting CD4 in helper T-cells, CD8 in cytotoxic T-cells, CD56 in NK-cells and CD45RO in memory T-cells. Histopathological examination revealed features of diffuse alveolar damage (DAD) with exudate in alveolar space and infiltration of inflammatory cells. Immunohistochemistry staining for CD4 showed weak to positive staining, CD8 showed weak positive staining, CD56 showed negative staining, while CD45RO showed a positive staining. It can be concluded that SARS-CoV-2 virus impaired innate immune response through a decrease in NK cells and adaptive immune response through a decrease in CD8 T cells which is one of the explanations of the destructive nature of SARS-CoV-2 virus.